Proceedings of the State Internal Improvement Convention (House document (Virginia. General Assembly. House of Delegates), 1848)
1848 State Internal Improvement Convention proceedings which was held on October 2, 1848 and submitted to the House of Delegates. Virginia Governor William Smith attached said proceedings and provided critical comments regarding some of the resolutions.